Modelling Persistence and Non-Linearities in the US Treasury 10-Year Bond Yields - Guglielmo Maria Caporale; Luis A. Gil-Alana; OlaOluwa Simon Yaya (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper analyses persistence and non-linearities in quarterly and monthly US Treasury 10-year bond yields over the period 1962-2021 using two different fractional integration approaches including Chebyshev polynomials and Fourier functions respectively. The results for both quarterly and monthly data provide evidence of non-linear structures and mean reversion (i.e., of transitory effects of shocks) under the assumption of autocorrelated errors.
Keywords: C22; E43; 330; non-linearities; Chebyshev polynomials; Fourier functions; persistence; US Treasury; 10-year bond yields